2011
DOI: 10.3349/ymj.2011.52.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to Predict Insignificant Prostate Cancer at Radical Prostatectomy in Korean Men: A Multi-Center Study

Abstract: PurposeDue to the availability of serum prostate specific antigen (PSA) testing, the detection rate of insignificant prostate cancer (IPC) is increasing. To ensure better treatment decisions, we developed a nomogram to predict the probability of IPC.Materials and MethodsThe study population consisted of 1,471 patients who were treated at multiple institutions by radical prostatectomy without neoadjuvant therapy from 1995 to 2008. We obtained nonrandom samples of n = 1,031 for nomogram development, leaving n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
8
0
3
Order By: Relevance
“…However, there are some reports that the reliability of the Epstein criteria can vary by race or regions. This implies that the significance of the Epstein criteria can be different between Western and Asian men 5. Some authors have reported that the Epstein criteria may be inaccurate in Asians with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some reports that the reliability of the Epstein criteria can vary by race or regions. This implies that the significance of the Epstein criteria can be different between Western and Asian men 5. Some authors have reported that the Epstein criteria may be inaccurate in Asians with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Choi et al reported the predictors for insignificant prostate cancer after RP in a Korean sample (22). They reviewed the pathological outcomes of 1471 men who were treated at multiple institutions in Korea.…”
mentioning
confidence: 99%
“…The characteristics of the study population are crucial in the performance of nomograms and ethnic differences in the behaviour of prostate cancer have been well documented . There are also nomograms in Asian men to predict pathological staging of prostate cancer . However, these nomograms were not constructed exclusively for the prediction of LN metastases and PLND was performed to a limited extent in most cases.…”
Section: Introductionmentioning
confidence: 99%